2016
DOI: 10.1586/17446651.2016.1145541
|View full text |Cite
|
Sign up to set email alerts
|

IDegAsp (insulin degludec + insulin aspart) for the management of type 2 diabetes: current status

Abstract: SUMMARYThe co-formulation insulin degludec/insulin aspart (IDegAsp) contains insulin degludec (IDeg), a basal insulin, and the rapid-acting insulin aspart (IAsp). Its unique pharmacodynamic profile provides a stable basal insulin action over a 24-h period due to the flat, ultra-long effect of IDeg, combined with prandial control from IAsp, which is unaffected by the basal component. IDegAsp provides a distinct mealtime insulin peak effect and reduces the likelihood of postprandial glucose excursions. The phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The formation of stable dihexamers in formulation also offers the potential for IDeg U100 to be co‐formulated with the rapid‐acting analogue insulin aspart without hybrid hexamers forming, or with liraglutide, a glucagon‐like peptide‐1 receptor agonist. The clinical utility of these fixed‐combination products has been demonstrated in several cohorts of patients with type 2 diabetes …”
Section: Multihexamer Chain Formation: Insulin Degludecmentioning
confidence: 99%
“…The formation of stable dihexamers in formulation also offers the potential for IDeg U100 to be co‐formulated with the rapid‐acting analogue insulin aspart without hybrid hexamers forming, or with liraglutide, a glucagon‐like peptide‐1 receptor agonist. The clinical utility of these fixed‐combination products has been demonstrated in several cohorts of patients with type 2 diabetes …”
Section: Multihexamer Chain Formation: Insulin Degludecmentioning
confidence: 99%
“…Insulin degludec/insulin aspart (IDegAsp; Ryzodeg ® ) is a novel co-formulation of 70% IDeg and 30% insulin aspart (IAsp, a rapid-acting insulin) administered as a single injection, either once or twice daily with main meals [ 2 ], wherein each insulin exerts its glucose-lowering effects without establishing interactions with the other agents [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…IDeg/Asp both has the characteristics of long-acting insulin and fast-acting insulin. Studies have found that compared with IGlar, IDeg/Asp could better control blood glucose and reduce the frequency of hypoglycemia events [10,18,22], but there have been few reports comparing efficacy and safety between IDeg/Asp and IGlar. Therefore, we conducted a meta-analysis of trials to evaluate and compare the efficacy and safety of IDeg/Asp and IGlar in the treatment of T2DM to provide a more beneficial comprehending and planning for clinical decision-making and future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, compared with insulin degludec/aspart (IDeg/Asp), insulin glargine (IGlar) is associated with a potential risk of hypoglycemia. IDeg/Asp combines IDeg and IAsp (7:3), which provides effective glycemic control, reduces hypoglycemia rate (particularly nocturnal hypoglycemia), allows a flexible injection time [10]. As the first coformulation of long-acting and short-acting insulin, IDeg/Asp retains its unique pharmacokinetic (PK) /pharmacodynamic (PD) properties [11].…”
mentioning
confidence: 99%